2015
DOI: 10.3164/jcbn.14-42
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial superoxide theory for oxidative stress diseases and aging

Abstract: Fridovich identified CuZnSOD in 1969 and manganese superoxide dismutase (MnSOD) in 1973, and proposed ”the Superoxide Theory,” which postulates that superoxide (O2•−) is the origin of most reactive oxygen species (ROS) and that it undergoes a chain reaction in a cell, playing a central role in the ROS producing system. Increased oxidative stress on an organism causes damage to cells, the smallest constituent unit of an organism, which can lead to the onset of a variety of chronic diseases, such as Alzheimer’s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
200
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(207 citation statements)
references
References 90 publications
3
200
0
4
Order By: Relevance
“…Furthermore, Mn-SOD influences the activity of transcription factors (such as HIF-1α, AP-1, NF-κB and p53) and affects DNA stability [35]. A critical role of Mn-SOD under physiological and pathological conditions has recently been reviewed in details and the following findings of Mn-SOD confirm the critical role of Mn-SOD in the survival of aerobic life [36][37][38][39]:…”
Section: Superoxide Dismutase In Biological Systemsmentioning
confidence: 82%
“…Furthermore, Mn-SOD influences the activity of transcription factors (such as HIF-1α, AP-1, NF-κB and p53) and affects DNA stability [35]. A critical role of Mn-SOD under physiological and pathological conditions has recently been reviewed in details and the following findings of Mn-SOD confirm the critical role of Mn-SOD in the survival of aerobic life [36][37][38][39]:…”
Section: Superoxide Dismutase In Biological Systemsmentioning
confidence: 82%
“…Due to the indispensable function in the processes of oxidative phosphorylation, Coenzyme Q-10 (CoQ-10) and its derivatives are the most prominent members in the family of Q/HQ [4][5][6][7]. Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…If the increase in free radicals is greater than the ability to neutralize them, ROS will attack cellular structures located near the sites where ROS are generated [30,44,48]. Functional imbalance between ROS levels and antioxidant concentrations can be caused by various disease states such as cancer, cardiovascular diseases, brain dysfunction, inflammatory diseases, neurodegenerative diseases, ischemiareperfusion injury, and aging [43,48,50,51].…”
Section: International Journal Of Physical Medicine and Rehabilitationmentioning
confidence: 99%
“…Under normal physiological conditions, this mitochondrial antioxidant defense system can adequately handles the potentially detrimental effects of ROS derived from energy metabolism, this cellular free-radical scavenging enzymes neutralize excess ROS and repair the enzymes that reverse ROSmediated damage [36,48]. However, when these enzymes cannot convert ROS such as the superoxide radical to H 2 O fast enough, oxidative damage occurs and accumulates in the mitochondria [29,30,49].…”
Section: International Journal Of Physical Medicine and Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation